Improved (G?/G)-Expansion Method for the Time-Fractional Biological Population Model and Cahn-Hilliard Equation - Baleanu, Dumitru; Ugurlu, Yavuz; İnç, Mustafa; Kilic, Bulent (Asme, 2015)
In this paper, we used improved (G'/G)-expansion method to reach the solutions for some nonlinear time-fractional partial differential equations (fPDE). The fPDE is reduced to an ordinary differential equation (ODE) by means of Riemann-Liouille derivative and a basic variable transformation. Various types of functions are obtained for the time-fractional biological population model (fBPM) and Cahn-Hilliard (fCH) equation.
Keywords: Backlund Transformation; Nonlinear Evolution; Diffusion